VITAL TESTAMENT AND THE AUTONOMY OF THE VULNERABLE SUBJECT (Isagoge - Journal of Humanities and Social Sciences, 2022)
This article aims to analyze the concept of autonomy correlated to the fundamental right to life, under a hermetic-philosophical prism, focusing on the importance of empowering terminally ill patients or people in irreversible medical conditions, based on the principle of human dignity.     The idea is to study the possibility of the autonomy, in some cases, implicates a self-limitation of the right to living, in the mentioned cases, making sure that they have a dignified death, befitting with their own individual and subjective concept of dignity. Thus, it is intended to show that, despite being a complex and delicate topic, it is also extremely relevant, requiring the debate and dissemination of information, enabling the self-determination of these subjects in effective ways, such as the directives of will.
Keywords: Dignified death; Freedom; Autodetermination; Vulnarability; Paul Ricoeur; Advance directives